2013
DOI: 10.1626/pps.16.95
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pythium and Phytophthora with Pre-emergence Seedling Damping-off of Soybean Grown in a FieldConverted from a Paddy Field in Japan

Abstract: In Japan, soybean is usually cultivated in fields that have been converted from rice paddies, and poor seedling establishment due to pre-emergence seedling damping-off is often observed during the rainy season. In this study, the factors that cause the damping-off in flooded soil were investigated under high soil moisture conditions in a greenhouse and in agricultural fields. In sterilized soil sampled from a soybean field, seedlings emerged well under 48-hr flooded conditions. In unsterilized soil, soybean se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…When seeds are physically injured, microbial infection can occur more easily, with infection by microbiological organisms being partly responsible for pre-emergence seedling rot under flooded conditions (Kato et al, 2013). In 5 cultivars, excluding 'Peking', the number of seedlings that did not produce root hairs and/or lateral roots increased under hypoxia and higher temperatures (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…When seeds are physically injured, microbial infection can occur more easily, with infection by microbiological organisms being partly responsible for pre-emergence seedling rot under flooded conditions (Kato et al, 2013). In 5 cultivars, excluding 'Peking', the number of seedlings that did not produce root hairs and/or lateral roots increased under hypoxia and higher temperatures (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because the infection by zoospores is essential to initiate the parasitic phase of the P. sojae life cycle, fields saturated for a long time provide one of the most ideal conditions for inducing Phytophthora root and stem rot. In Japan, most soybean plants are cultivated in fields converted from rice paddies ( Kato et al, 2013 ; Sugimoto et al, 2012 ). Such soybean fields usually contain poorly drained soil with a high moisture level, which is ideal for a P. sojae infection and subsequent multiplication.…”
mentioning
confidence: 99%
“…Kokuryu et al (2010) reported that the inhibition of the seedling establishment was attributed to the imbibition damage, soil microorganisms and soil surface strength. Kato et al (2013) reported that microorganisms especially oomycetes are involved in the flooding damage. Accordingly, these problems need to be solved to reduce the flooding damage of soybean seedlings.…”
mentioning
confidence: 99%
“…However, the result did not deny the possibility that the improvement might also be caused by a mechanism other than the inhibition of the generation of sulfide ions. For example, the molybdenum compound might improve the seedling establishment by directly inhibiting the multiplication of microorganisms like the microbicide, because Kato et al (2013) reported that a microbicide improved the establishment of soybean seedlings under a flooded condition. Nakayama et al (2005) pointed out a difference in the flooding damage of soybean before and after radicle protrusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation